Blood loss and the need for transfusion after shoulder surface replacement. Issue 2 (20th March 2013) - Singh, Vinay Kumar; Trehan, Ravi; Banerjee, Samik; Bardakos, Nikolaos V.; Patel, Vipul R.
ABSTRACT: Background: Studies on stemmed primary shoulder arthroplasty have shown transfusion rates of up to 38%. The present study aimed to evaluate blood loss and the need for blood transfusion after primary humeral and total shoulder surface replacement. Materials and methods: Patients undergoing both primary humeral head ( n  = 20) and total shoulder ( n  = 63) resurfacing were included. The mean drop in haemoglobin levels on the first postoperative day and the need for transfusion were recorded and analyzed against the patient's age, sex, body mass index, American Society of Anesthesiologists grade, type of surgery performed, pre‐operative haemoglobin and the use of tranexamic acid. Results: Only one patient in the entire series (1.2%) required blood transfusion postoperatively, following total shoulder resurfacing. There were statistically significant differences between the two groups with respect to estimated blood loss ( p  = 0.005), duration of surgery ( p  < 0.0005) and haemoglobin drop ( p < 0.0005), all in favour of the humeral head resurfacing group. The type of surgery was the only independent factor significantly affecting the reduction of haemoglobin levels postoperatively ( p  < 0.0005). Conclusions: Surface replacement of the shoulder appears to be associated with reduced blood loss, leading to a very low need for blood transfusion.